NOTE ON THE LOCOMOTORY BEHAVIOUR OF THE MUDSKIPPER BOLEOPHTHALMUS BODDARTI - De, J K; Nandi, N C (Indian Journal of Fisheries, 2011)
Boleophthalmus bpddarti, besides swimming, displays four modes oflocomotion, viz., crutching, skipping, skimming and climbing. Locomotion bycrutching is to acquire fixxl, skipping and skimming to escape and climbing torest. Significance of such locomotory behaviours has been outlined.